Comprehensive Analysis of Differentially Expressed Long Noncoding RNA-mRNA in the Adenoma-Carcinoma Sequence of DNA Mismatch Repair Proficient Colon Cancer. (9th June 2021) - Li, Wenkun; Li, Qian; Ge, Jiang; Wang, Yun; Li, Nanshan; Lao, Yueqiong; Wang, Yadan; Liu, Kuiliang; Guo, Chunmei; Lin, Wu; Jiang, Guojun; Wei, Nan; et al.
Abstract : DNA proficient mismatch repair colon cancer (pMMR CC) is the most common subtype of sporadic CC. We aimed to investigate the role of long noncoding RNAs (lncRNAs) in pMMR CC carcinogenesis. In the present study, we conducted transcriptomic analysis of lncRNAs-mRNAs in five low-grade intraepithelial neoplasia (LGIN), five high-grade intraepithelial neoplasia (HGIN), four pMMR CC, and five normal control (NC) tissues. Gene Ontology (GO), Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment pathway, and coexpression network analyses were performed to elucidate the functions of lncRNAs and mRNAs as well as their interactions. Quantitative real-time polymerase chain reaction (qRT-PCR) was used to validate five dysregulated lncRNAs in a large set of colon tissues. Receiver-operating characteristic (ROC) curves were employed to evaluate the performance of the candidate lncRNAs. A set of 5783 differentially expressed lncRNAs and 4483 differentially expressed mRNAs were detected among the LGIN, HGIN, pMMR CC, and NC samples. These differentially expressed lncRNAs and mRNAs were assigned to 275 significant GO terms and 179 significant KEGG enriched pathways. qRT-PCR confirmed that the expression of five selected lncRNAs (ENST00000521815, ENST00000603052, ENST00000609220, NR_026543, and ENST00000545920) were consistent with the microarray data. ROC analysis showed that four lncRNAs (ENST00000521815, ENST00000603052, ENST00000609220, and NR_026543) had larger area under the ROC curve (AUC) values compared to serum carcinoembryonic antigens, thereby distinguishing NC from pMMR CC. In conclusion, several lncRNAs play various roles in the adenoma-carcinoma sequence and may serve as potential biomarkers for the early diagnosis of pMMR CC.